On resolving sets in the point-line incidence graph of PG(n, q) - Bartoli, Daniele (Ars mathematica contemporanea, 2020)
Lower and upper bounds on the size of resolving sets and semi-resolving sets for the point-line incidence graph of the finite projective space ?$PG(n, q)$? are presented. It is proved that if ?$n > 2$? is fixed, then the metric dimension of the graph is asymptotically ?$2q^{n-1}$?.
Keywords: finite projective spaces; incidenčni graf točk in premic; končni projektivni prostor; point-line incidence graph; resolvenčna množica; resolving sets